The Impact of Peer Interaction and Gadget Addiction on the Subjective Wellbeing of 5–6-Year-Old Children in Java, Indonesia: A Quantitative Study - Saroinsong, W.P; Nursalim, M; Azmawaty Binti Mohamad Nor (Universitas PGRI Yogyakarta, 2025)
The advancement of digital technology has altered children's social interactions, particularly in Indonesia, where early gadget use may limit direct peer contact and impede social-emotional development. Although positive peer relationships are essential for children's subjective well-being, studies examining the link between gadget addiction, peer interaction, and well-being in early childhood within a local cultural context are still scarce. This quantitative study surveyed 400 children aged 5–6 years in Java, Indonesia, using questionnaires on peer relationships, gadget addiction, and well-being. Multiple linear regression and path analysis revealed that peer interaction significantly influences subjective well-being (β = 0.362, p < 0.001), while gadget addiction was not directly significant (β = 0.013, p = 0.165). Gadget use, however, served as a mediating variable. These findings emphasize the importance of promoting strong peer interactions and managing screen exposure to support emotional and social development in early childhood. Keywords: peers; children, subjective well-being, gadget addiction